2021
DOI: 10.25259/ijpc_160_21
|View full text |Cite
|
Sign up to set email alerts
|

“Post-COVID-19 syndrome:” The New Pandemic Affecting Healthcare Workers and How the Frontline Warriors Are Battling it

Abstract: Objectives: “Post-COVID-19 syndrome,” which may be the new pandemic, has affected various domains of quality of life; even among those who have recovered from mild COVID-19 disease. The aim of our study was to explore the health, social and psychological impact on healthcare workers (HCWs) who have recovered from active COVID-19 illness and highlight their needs post-recovery. Materials and Methods: It was a web-based survey study. A total of 163 eligible consenting HCWs participated in this survey. The Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Tiredness or fatigue is one of the most frequently described long COVID symptoms in the literature [ 33 ]. PCS was reported more frequently in COVID-19 patients who were hospitalised than those not hospitalised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiredness or fatigue is one of the most frequently described long COVID symptoms in the literature [ 33 ]. PCS was reported more frequently in COVID-19 patients who were hospitalised than those not hospitalised.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, attention should be paid to the financial consequences of COVID-19 and PCS. As is pointed out by a working group from India, one-third of the HW are worried about the financial impact of PCS on them and their families [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…After COVID-19 infection, the return to work and to usual physical capability may not be so easy. In fact, the long COVID phenomenon is emerging, significantly increasing the interval between infection and the return to work [ 12 ] due to physical and psychological symptoms caused by the disease [ 13 , 14 ]. As the incidence of COVID-19 among HCWs is high, the impact of persistent disturbances after the acute illness can also have negative effects on the broader healthcare delivery system, resulting in a possible loss of skilled healthcare personnel due to post-COVID-19 disabilities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on HCWs showed similar results [ 25 27 ]. Reported incidence of post-COVID-19 syndrome reached 73% in a study including 2053 participants working in health care and social services in Germany.…”
Section: Discussionmentioning
confidence: 58%